Pengalaman Wisata dan Citra Destinasi: Sebuah Kajian Pustaka Sistematis - Abrian, Youmil; Wardi, Yunia; Abror, Abror; Dwita, Vidyarini; Evanita, Susi (Lasigo Akademia Indonesia, 2023)
The purpose of this study is to identify and analyze several key references regarding tourist experience and destination image. This research is a systematic literature review using the Scopus-based science citation index. Based on several stages of the systematic review method, this study found 41 key references from Scopus indexed journals. This study also examined citation behavior based on quartile and cite score. This study found that the journal sustainability Switzerland is the journal that discusses the most about tourism experience and destination image. However, most of the articles are published in business and management journals and also journals are published in the field of tourism, while for the country of origin of researchers, the United Kingdom is the most dominant country of origin of researchers followed by researchers from China and the United States. Thus, there are opportunities for further research in the context of tourism. This study contributes to further research and makes a significant contribution in answering research questions or addressing issues in the field of tourism.